O processo de alfabetização de uma criança com deficiência intelectual no 1º ano do ensino fundamental - Mesquita, Guida (2015)
The study analyzes how the literacy of a child with learning disability happens in the first year of elementary school. Observes the pedagogical work done regularly in common classroom on literacy and how the Specialized Educational Services are being done. Uses a qualitative methodology with a case study of ethnographic type to observe a child‟s daily school routine. The theoretical perspective adopted in this study are based on the presuppositions of Bakhtin, who argued for a dialogic approach, and in the studies of Vigotski, which addresses the issue of learning through mediation with others, observing, also, other authors who brings a cultural- historical approach weaving their speech about special education and literacy. The data was collected through participants observation, interviews with those involved in the research, records of daily field work, photographs, analyses of school documents, reports of children with intellectual disability. With this analyses, it was observed that the child does the activities of reading and writing accompanied by the teacher and by the trainee, identifies and write‟s his name, recognizes the letters in the alphabet, can count history books making reading of images, makes activities in notebook and textbook, participates in all events, read and write a few words. The Multifunction Resource Room has contributed a lot in learning Estrelinha, subject of this study. The curriculum differentiation is part of the main indicators in the effectiveness of inclusion and, consequently, learning. There was a communication link between lounge professionals and of Multifunction Resource Room, therefore the activities were still being worked on Specialized Educational Services, but differently, using other materials. Note that the Specialized Educational Services is a legitimate space for learning of cultural knowledge by children with intellectual disabilities, among them, the written language. In the classrooms, she participates using speech to interact in all activities, participates in group activities, answers the questions asked by the teacher, but, when the child needs to write what he has already learned, still requires a longer time to finish the task and needs individual guidance of either the trainee or the teacher. All educational work done by the professionals involved contributed so the child could gain the reading and writing results as reported, but, there is continuity in monitoring this child, new advances will be obtained up to the moment in which he will be able to make it on his own. In results show that participation of others in the acquisition process of reading and of writing contributed in the intellectual development of this child with regards to their participation in activities, in perception, in reasoning, in speech, in writing, in interacting with the group and in his relationship with people